Hard carbon negative electrode material based on mixed traditional Chinese medicine residues as well as preparation method and application of hard carbon negative electrode material

Through the preparation method based on mixed Chinese medicine residue, including pretreatment, pre-carbonization, hydrothermal heating, activation and carbonization, the problems of low cost performance and complex operation in the prior art are solved, and efficient and low-cost hard carbon negative electrode material preparation is achieved, with excellent sodium ion battery performance.

CN119750577APending Publication Date: 2025-04-04CHONGQING JIAOTONG UNIV +1

Patent Information

Application Number
CN202411952112.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The method of preparing hard carbon negative electrode materials in the prior art is not cost-effective, complicated in operation, and acidic pretreatment will lead to the removal of hemicellulose and lignin in the Chinese medicine residue, which is not conducive to application in sodium ion batteries.

Method used

The preparation method based on mixed Chinese medicine residue is adopted, including pretreatment, pre-carbonization, hydrothermal heating, activation and carbonization, and catalyzed dehydroxylation and water through an activator to form a porous structure and improve the active site of sodium storage.

Benefits of technology

It has achieved the characteristics of low cost, high carbon yield, simple preparation, high safety and high reaction efficiency. The prepared hard carbon negative electrode material exhibits excellent specific capacity and charge and discharge efficiency in sodium ion batteries, with a reversible capacity of up to 386mAh/g.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215101850000051
    Figure BDA0005215101850000051
Patent Text Reader

Abstract

A preparation method of a hard carbon negative electrode material based on mixed traditional Chinese medicine residues relates to the technical field of hard carbon materials, and comprises the following steps: S1, pretreating the mixed traditional Chinese medicine residues to obtain mixed traditional Chinese medicine residue powder; s2, pre-carbonizing the mixed traditional Chinese medicine residue powder obtained in S1; s3, soaking the mixed traditional Chinese medicine residue powder pre-carbonized in S2 in an activator saturated solution, uniformly stirring, heating by a hydrothermal method, and drying for later use; s4, activating and carbonizing the mixed traditional Chinese medicine residue powder dried in S3; s5, performing acid pickling, water washing, suction filtration, drying and filtration on the mixed traditional Chinese medicine residue powder carbonized in the step S4 to obtain the hard carbon negative electrode material; the invention also provides the hard carbon negative electrode material prepared by the method and application of the hard carbon negative electrode material in a sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hard carbon materials, and in particular to a hard carbon negative electrode material based on mixed traditional Chinese medicine residues, and a preparation method and application thereof. Background Art

[0002] Hard carbon material is a non-graphitized carbon material, whose main feature is disordered structure. It also has the characteristics of wide source of raw materials, simple synthesis method and relatively low cost. Due to its unique structure and excellent electrochemical properties, hard carbon material has good application prospects in sodium ion batteries.

[0003] With the country's emphasis on the traditional Chinese medicine industry and the development of the field of traditional Chinese medicine, the amount of traditional Chinese medicine residues produced is also increasing year by year. If a large amount of traditional Chinese medicine residues are not effectively treated and utilized, it will pollute the environment. Some companies have begun to explore ways to utilize traditional Chinese medicine residues as resources, such as producing organic fertilizers and extracting effective ingredients. However, due to the limitations of technology and cost factors, the recycling of traditional Chinese medicine residues still faces some challenges. Therefore, finding a high-value-added transformation method for traditional Chinese medicine residues is conducive to reducing environmental pollution, improving ecological balance, and efficient utilization of waste resources.

[0004] In order to achieve the above purpose, in the Chinese invention patent with the authorization announcement number CN107579249B, a hard carbon negative electrode material prepared from medicinal residues and a preparation method thereof are disclosed, which uses a relatively high concentration of hydrochloric acid to treat the Chinese medicinal residues of rhizomes and fruit shells, and combines the modification treatment to reduce the loss of lithium ions, and the hard carbon material finally prepared has a high first coulomb efficiency and a high discharge capacity; however, the acid pretreatment will remove a large amount of hemicellulose and lignin in the Chinese medicinal residues, which is not conducive to application in sodium ion batteries, and the patent selects wet ball milling and classification after carbonization to obtain the hard carbon negative electrode material, and the process is redundant and cumbersome. In the Chinese invention patent with the publication number CN116573644A, a sodium ion battery hard carbon negative electrode material and method prepared using Chinese medicinal residues are disclosed, which obtains the sodium ion hard carbon negative electrode material by pretreatment, freeze drying, precarbonization, heating reflux and calcination in alternating manner, and shows good performance in sodium batteries, but the patent adopts the heating reflux and calcination alternating manner, which is too complicated to operate. Summary of the invention

[0005] In view of the deficiencies in the prior art, the invention provides a hard carbon negative electrode material based on mixed traditional Chinese medicine residues and a preparation method and application thereof, which solves the problems of low cost performance and complex operation of the method for preparing hard carbon negative electrode materials in the prior art.

[0006] A method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues comprises the following steps:

[0007] S1. Pre-treating the mixed Chinese medicine residue to obtain a mixed Chinese medicine residue powder;

[0008] S2. Pre-carbonizing the mixed Chinese medicine residue powder obtained in S1;

[0009] S3. The pre-carbonized mixed Chinese medicine residue powder in S2 is immersed in a saturated solution of an activator and stirred, and then heated by a hydrothermal method and dried for use;

[0010] S4. Activate and carbonize the mixed Chinese medicine residue powder after drying in S3;

[0011] S5. The mixed Chinese medicine residue powder carbonized in S4 is subjected to acid washing, water washing, suction filtration, drying and filtering to obtain a hard carbon negative electrode material.

[0012] Preferably, in step S1, the mixed Chinese medicine residue includes at least one of wormwood leaf and ginkgo leaf, as well as coptis root, white peony root, ligusticum chuanxiong, radix cyperi multiflorum, tangerine peel and jujube.

[0013] Preferably, in step S1, the pretreatment method is to dry the mixed Chinese medicine residue at 80-120° C. for 4-12 hours and then grind it for 30-60 seconds.

[0014] Preferably, in step S2, the pre-carbonization temperature is 300-400°C, and the pre-carbonization time is 1-2 hours.

[0015] Preferably, in step S3, the activator includes at least one of zinc chloride, potassium hydroxide, phosphoric acid and sodium hydroxide, the mass ratio of the pre-carbonized mixed Chinese medicinal residue powder to the activator is 1:1-4, and the soaking time is 12-24 hours.

[0016] Preferably, in step S3, the hydrothermal temperature is 165-185° C., and the heating time is 6-10 h.

[0017] Preferably, in step S4, the activation temperature is 500-700°C, the carbonization temperature is 800-1400°C, the heating rates of activation and carbonization are both 1-10°C / min, and the holding time of activation and carbonization is both 1-3h.

[0018] Preferably, in step S5, a hydrochloric acid solution with a concentration of 0.1M to 2M is used for pickling, stirring is required for 12 to 24 hours during the pickling process, and the filtration screen is 100 to 500 meshes.

[0019] The invention also provides a hard carbon negative electrode material based on mixed traditional Chinese medicine residues, which is prepared by the preparation method.

[0020] The present invention also provides an application of a hard carbon negative electrode material based on mixed traditional Chinese medicine residues in a sodium ion battery.

[0021] Compared with the prior art, the invention has the following beneficial effects:

[0022] 1. The preparation method of the present invention has the characteristics of low cost, high carbon yield, simple preparation, high safety, high reaction efficiency, etc.; the present invention prepares the mixed Chinese medicine residue into a hard carbon negative electrode material by simply pyrolyzing and carbonizing it, so that it can be used in sodium ion batteries, making it a product with high added value, meeting the environmental requirements of green resources, and realizing the efficient utilization of waste resources.

[0023] 2. During the entire heat treatment process of the present invention, the activator catalyzes the dehydroxylation and water removal during hydrothermal heating, and then reacts with the carbon to gasify during the activation process, forming a porous structure on the carbon surface. Finally, during the carbonization process, the amorphous components in the mixed Chinese medicine residue form a closed-pore hollow structure at the porous structure, which reduces the specific surface area while providing more sodium storage active sites, thereby increasing the capacity for sodium ions.

[0024] 3. The hard carbon negative electrode material of the present invention is used in sodium ion batteries, and has good specific capacity and charge and discharge efficiency. The maximum reversible capacity can reach 386 mAh / g at a current density of 0.1 A / g. It has excellent energy storage capacity and good commercial value.

[0025] Other advantages, objectives and features of the invention will be reflected in part through the following description, and in part will be understood by those skilled in the art through study and practice of the invention. DETAILED DESCRIPTION

[0026] In order to make the technical means, creative features, purpose and function of the invention clearer and easier to understand, the invention is further explained below in conjunction with specific implementation methods:

[0027] Example 1

[0028] S1. The mixed Chinese medicine residue was dried in a vacuum oven at 80 ° C for 12 h, and then ground in a wall breaking machine for 30S to obtain a mixed Chinese medicine residue powder;

[0029] S2. The mixed Chinese medicine slag powder in S1 was placed in a tubular furnace for pre-carbonization under a nitrogen atmosphere at a pre-carbonization temperature of 300°C for a pre-carbonization time of 2h;

[0030] S3. Soak the pre-carbonized mixed Chinese medicine residue powder in S2 in a saturated zinc chloride solution for 24 hours and stir thoroughly, wherein the mass ratio of the mixed Chinese medicine residue powder to zinc chloride is 1:1, and then heat to 165°C in a hydrothermal autoclave and maintain for 10 hours, and then filter and dry;

[0031] S4. The mixed Chinese medicine residue powder after drying in S3 was placed in a tubular furnace and heated to 500°C at a rate of 5°C / min for activation under a nitrogen atmosphere, and kept warm for 2h, and then heated to 1000°C at a rate of 5°C / min for carbonization, and kept warm for 2h;

[0032] S5. The mixed Chinese medicine residue powder carbonized in S4 was immersed in a 2M hydrochloric acid solution and stirred for 12 hours, and then washed with water, filtered, dried, and passed through a 100-mesh sieve to obtain a hard carbon negative electrode material based on the mixed Chinese medicine residue.

[0033] Example 2

[0034] S1. The mixed Chinese medicine residue was dried in a vacuum oven at 100 ° C for 6 h, and then ground in a wall breaking machine for 40S to obtain a mixed Chinese medicine residue powder;

[0035] S2. The mixed Chinese medicine slag powder in S1 is placed in a tubular furnace for pre-carbonization under a nitrogen atmosphere at a pre-carbonization temperature of 400°C for a pre-carbonization time of 1 h;

[0036] S3. The mixed Chinese medicine residue powder pre-carbonized in S2 was immersed in a potassium hydroxide solution for 16 hours and stirred thoroughly, wherein the mass ratio of the mixed Chinese medicine residue powder to potassium hydroxide was 1:4, and then heated to 180°C in a hydrothermal autoclave and maintained for 6 hours, and then filtered and dried;

[0037] S4. The mixed Chinese medicine residue powder after drying in S3 was placed in a tubular furnace and heated to 600°C at a rate of 1°C / min for activation under a nitrogen atmosphere, and kept warm for 3 hours, and then heated to 1200°C at a rate of 10°C / min for carbonization, and kept warm for 1 hour;

[0038] S5. The mixed Chinese medicine residue powder carbonized in S4 was immersed in a 1M hydrochloric acid solution and stirred for 18 hours, and then washed with water, filtered, dried, and passed through a 200-mesh sieve to obtain a hard carbon negative electrode material based on the mixed Chinese medicine residue.

[0039] Example 3

[0040] S1. The mixed Chinese medicine residue was dried in a vacuum oven at 90 ° C for 8h, and then ground in a wall breaking machine for 60S to obtain a mixed Chinese medicine residue powder;

[0041] S2. The mixed Chinese medicine slag powder in S1 was placed in a tubular furnace for pre-carbonization under a nitrogen atmosphere at a pre-carbonization temperature of 350°C for a pre-carbonization time of 1.5 h;

[0042] S3. The mixed Chinese medicine residue powder pre-carbonized in S2 was immersed in a phosphoric acid solution for 24 hours and stirred thoroughly, wherein the mass ratio of the mixed Chinese medicine residue powder to phosphoric acid was 1:4, and then heated to 175°C in a hydrothermal autoclave and maintained for 7 hours, and then filtered and dried;

[0043] S4. The mixed Chinese medicine residue powder after drying in S3 was placed in a tubular furnace and heated to 700°C at a rate of 10°C / min for activation under a nitrogen atmosphere, and kept warm for 1h, and then heated to 1400°C at a rate of 1°C / min for carbonization, and kept warm for 3h;

[0044] S5. The mixed Chinese medicine residue powder carbonized in S4 was immersed in a 0.1M hydrochloric acid solution and stirred for 24 hours, and then washed with water, filtered, dried, and passed through a 500-mesh sieve to obtain a hard carbon negative electrode material based on the mixed Chinese medicine residue.

[0045] Example 4

[0046] S1. The mixed Chinese medicine residue was dried in a vacuum oven at 120 ° C for 4h, and then ground in a wall breaking machine for 50S to obtain a mixed Chinese medicine residue powder;

[0047] S2. The mixed Chinese medicine residue powder in S1 was placed in a tubular furnace for pre-carbonization under a nitrogen atmosphere at a pre-carbonization temperature of 400°C for a pre-carbonization time of 1.5 h;

[0048] S3. The mixed Chinese medicine residue powder pre-carbonized in S2 was immersed in a sodium hydroxide solution for 12 hours and stirred thoroughly, wherein the mass ratio of the mixed Chinese medicine residue powder to sodium hydroxide was 1:2, and then heated to 185°C in a hydrothermal autoclave and maintained for 6 hours, and then filtered and dried;

[0049] S4. The mixed Chinese medicine residue powder after drying in S3 was placed in a tubular furnace and heated to 500°C at a rate of 7°C / min for activation under a nitrogen atmosphere, and kept warm for 2h, and then heated to 800°C at a rate of 3°C / min for carbonization, and kept warm for 2h;

[0050] S5. The mixed Chinese medicine residue powder carbonized in S4 was immersed in a 1M hydrochloric acid solution and stirred for 16 hours, and then washed with water, filtered, dried, and passed through a 400-mesh sieve to obtain a hard carbon negative electrode material based on the mixed Chinese medicine residue.

[0051] Comparative Example 1

[0052] Compared with Example 1, the ratio of pre-carbonized Chinese medicine residue powder to zinc chloride is 5:1, and the remaining steps are the same.

[0053] Comparative Example 2

[0054] Compared with Example 1, the ratio of pre-carbonized Chinese medicine residue powder to zinc chloride is 1:10, and the remaining steps are the same.

[0055] Comparative Example 3

[0056] Compared with Example 1, the carbonization temperature is 600° C., and the remaining steps are the same.

[0057] Comparative Example 4

[0058] Compared with Example 1, the carbonization temperature is 1600° C., and the remaining steps are the same.

[0059] The electrode performance tests were conducted on the hard carbon negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-4 respectively. The test conditions were as follows: by mass fraction, the negative electrode was composed of 80% hard carbon negative electrode material, 10% Super P and 10% sodium alginate, deionized water was used as the diluent, the glass fiber separator was used as the sodium battery separator, the copper foil was used as the current collector, and 1 mol / L NaPF 6 -DME solution was used as the electrolyte. Constant current charge and discharge performance test was carried out on the NEWARE charge and discharge instrument. The current density was 0.1A / g and the voltage range was 0.01~3V. Super P was a small particle conductive carbon black. NaPF 6 -DME solution is a solution with pure 1,2-dimethoxyethane as solvent and sodium hexafluorophosphate as solute. The final electrochemical performance results are shown in the following table.

[0060]

[0061] It can be seen from the above table that the hard carbon negative electrode materials based on mixed traditional Chinese medicine slag prepared in Examples 1-4 all exhibit good electrochemical properties. The reversible capacity can reach up to 386 mAh / g at a current density of 0.1 A / g, and the coulombic efficiency can reach up to 86%. Under appropriate raw material ratios, the reversible capacity at 0.1 A / g exceeds 350 mAh / g, and the coulombic efficiency is greater than 79%, indicating that the hard carbon negative electrode material obtained by pretreating, precarbonizing, hydrothermal method, activating and carbonizing the mixed traditional Chinese medicine slag in the present invention has good effects and can effectively improve the sodium storage performance of the hard carbon negative electrode material.

[0062] In Comparative Example 1, a small amount of zinc chloride activator was added during preparation, and its reversible capacity at a current density of 0.1 A / g was 258 mAh / g, and the first coulombic efficiency was 66%. Compared with Example 1, the electrochemical performance was poor. This was because the amount of activator added was too small, resulting in failure to fully react with the carbon element in the mixed Chinese medicine residue, resulting in an underdeveloped pore structure, a small specific surface area, and insufficient pore volume, and failure to provide more sodium ion active sites, so the sodium storage performance was slightly poor.

[0063] In Comparative Example 2, an excessive amount of zinc chloride activator was added during preparation, and its reversible capacity at a current density of 0.1 A / g was 216 mAh / g, and the first coulombic efficiency was 59%. Compared with Example 1, the electrochemical performance was poor. This was because the excessive amount of activator added resulted in the pore structure of the carbon after carbonization of the mixed traditional Chinese medicine slag being too large and causing its structure to collapse. The pore volume was insufficient and more sodium ion active sites could not be provided, so the sodium storage performance was slightly poor.

[0064] In Comparative Example 3, when the carbonization temperature is low during the carbonization process, the reversible capacity at a current density of 0.1 A / g is 226 mAh / g, and the first coulombic efficiency is 64%. The electrochemical performance is poor compared with that in Example 1. This is because when the carbonization temperature is low, the degree of graphitization of the hard carbon prepared from the mixed traditional Chinese medicine slag is seriously insufficient, the interlayer spacing is small, and it is not conducive to the insertion and deintercalation of sodium ions, thereby affecting the capacity of the sodium ion battery.

[0065] In Comparative Example 4, when the carbonization temperature is high during the carbonization process, the reversible capacity at a current density of 0.1 A / g is 231 mAh / g, and the first coulombic efficiency is 69%. The electrochemical performance is poorer than that of Example 1. This is because when the carbonization temperature is high, the hard carbon prepared from the traditional Chinese medicine residue has a high degree of graphitization, the interlayer spacing is reduced, and the pore structure of the hard carbon structure is contracted, which is not conducive to the insertion and deintercalation of sodium ions, thereby affecting the capacity of the sodium ion battery.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the invention rather than to limit it. Although the invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the invention, which should be included in the scope of the claims of the invention.

Claims

1. A method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues, characterized in that: The following steps are involved: S1. Pre-treating the mixed Chinese medicine residue to obtain a mixed Chinese medicine residue powder; S2. Pre-carbonizing the mixed Chinese medicine residue powder obtained in S1; S3. The pre-carbonized mixed Chinese medicine residue powder in S2 is immersed in a saturated solution of an activator and stirred, and then heated by a hydrothermal method and dried for use; S4. Activate and carbonize the mixed Chinese medicine residue powder after drying in S3; S5. The mixed Chinese medicine residue powder carbonized in S4 is subjected to acid washing, water washing, suction filtration, drying and filtering to obtain a hard carbon negative electrode material.

2. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S1, the mixed Chinese medicine residue includes at least one of wormwood leaf and ginkgo leaf, as well as coptis root, white peony root, ligusticum chuanxiong, radix cyperi multiflorum, tangerine peel and jujube.

3. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S1, the pretreatment method is to dry the mixed Chinese medicine residue at 80-120° C. for 4-12 hours and then grind it for 30-60 seconds.

4. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S2, the pre-carbonization temperature is 300-400°C, and the pre-carbonization time is 1-2 hours.

5. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S3, the activator includes at least one of zinc chloride, potassium hydroxide, phosphoric acid and sodium hydroxide, the mass ratio of the pre-carbonized mixed Chinese medicine residue powder to the activator is 1:1-4, and the soaking time is 12-24 hours.

6. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S3, the hydrothermal temperature is 165-185° C., and the heating time is 6-10 hours.

7. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S4, the activation temperature is 500-700°C, the carbonization temperature is 800-1400°C, the heating rates of activation and carbonization are both 1-10°C / min, and the holding time of activation and carbonization is both 1-3h.

8. The method for preparing a hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 1, characterized in that: In step S5, a hydrochloric acid solution with a concentration of 0.1M to 2M is used for pickling. The pickling process needs to be stirred for 12 to 24 hours, and the filtration screen is 100 to 500 meshes.

9. A hard carbon negative electrode material based on mixed traditional Chinese medicine residues, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the hard carbon negative electrode material based on mixed traditional Chinese medicine residues according to claim 9 in sodium ion batteries.

Citation Information

Patent Citations

  • A method for preparing hard carbon anode materials from traditional Chinese medicine residues.

    CN107579249B

  • Sodium-ion battery hard carbon negative electrode material prepared from traditional Chinese medicine residues and preparation method of sodium-ion battery hard carbon negative electrode material

    CN116573644A

  • Method for preparing biomass carbon material from traditional Chinese medicine waste residues

    CN115483039A

Cited By

  • Traditional Chinese medicine residue-based hard carbon negative electrode material with soft and hard carbon core-shell structure as well as preparation method and application of traditional Chinese medicine residue-based hard carbon negative electrode material

    CN121672475A